Economic Planning and Industrial Policy in the Globalizing Economy: Concepts, Experience and Prospects - Yülek, Murat (Springer, 2015)
This book discusses national development planning in the context of a globalized world economy. National economic development planning, the process of defining strategic economic objectives for a country and designing policies and institutional frameworks to attain them, was popular in many countries in the 1960s and 1970s. Over time it lost its appeal. More recently, with globalization accelerating and economic competition increasing, it is making a comeback in different countries under different forms. National planning in this new era is different than the earlier quantitative planning approaches. It employs different tools, such as strategic visions and action plans, revived forms of physical infrastructure planning, industrial policy, and cluster policy. Built on the research of international scholars with firsthand knowledge of the countries in question, this volume presents and evaluates current national planning strategies and policy worldwide. It will be of interest to both academicians who study and teach globalization and development as well as policy makers who may use it as a reference as they contemplate their own strategies.